MASTICATORY EFFICIENCY AS CRITERION OF ESTIMATION OF FUNCTIONAL STATE OF DENTOALVEOLAR SYSTEM - D.M. Korol; M.D. Korol; I.V. Skubii; D.D. Kindii; Ye.D. Toncheva; V.V. Yakrovyi (Український стоматологічний альманах)
Masticatory efficiency is one of the most important problems of human’s dental health.